Pemberdayaan Ekonomi Masyarakat Melalui Pelatihan Pengembangan UMKM Kue Bawang dan Kue Telunjuk di Desa Baharu - Riski; Farah, Siti; Nurlaila, Nurlaila; Niatera, Niatera; Adria, Adria (FLEKSIBEL: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to empower the economy of the people in Desa Baharu, Blang Pidie District, Southwest Aceh Regency, through training and development of SMEs, specifically in the production of fried onion snacks and finger cookies. The training includes enhancing technical skills in production, digital marketing through social media, and more effective business management. The methods used in this activity include lectures, interactive discussions, and hands-on practices supported by the use of social media as a marketing tool. The results of the training show significant improvements in product quality and marketing capabilities, with many participants starting to utilize social media to reach a broader market. Additionally, SME owners demonstrated better management of business finances in a more systematic way. It is expected that this training will strengthen SMEs in Desa Baharu, improve product competitiveness, and have a positive impact on the local economy.